Tris-(2-pyridylmethyl)amine-ligated Cu(ii) 1, 3-diketonate complexes: anaerobic retro-Claisen and dehalogenation reactivity of 2-chloro-1, 3-diketonate derivatives. Issue 5 (15th January 2021) - Elsberg, Josiah G. D.; Anderson, Stephen N.; Tierney, David L.; Reinheimer, Eric W.; Berreau, Lisa M.
Abstract : Six-coordinate Cu(ii ) diketonate complexes were isolated and characterized; TPA-ligated Cu(ii ) chlorodiketonate derivatives exhibit anaerobic retro-Claisen reactivity. Abstract : We report synthetic, structural and reactivity investigations of tris-(2-pyridylmethyl)amine (TPA)-ligated Cu(ii ) 1, 3-diketonate complexes. These complexes exhibit anaerobic retro-Claisen type C–C bond cleavage reactivity which exceeds that found in analogs supported by chelate ligands with fewer and/or weaker pyridyl interactions.